Privacy concerns toward short-form video platforms: Scale development and validation - Wang, Qingqing; Zhang, Wensong; Wang, Haikun (Frontiers in Psychology, 2022)
Privacy concerns can well explain the usage tendency between users and short-form video platforms, but existing studies lack measures of multidimensional scales of privacy concerns. To this end, this study takes the existing privacy concern theory as the basis for scale development, and on the basis of fully considering the CFIP scale, Sheehan and Hoy scale, IUPIC scale, and Hong and Thong IPC scale, combined with the existing privacy concern related research. Three representative short-form video platforms, Tik Tok, Kuaishou, and Xigua, were selected as the theoretical samples. We explored the concept and constitutive dimensions of privacy concern, developed a privacy concern scale through qualitative interviews and open-ended questionnaires, and applied SPSS24.0 and Mplus 7.0 to test the privacy concern scale. The results of this study found that privacy concerns consisted of three dimensions: collection concerns, awareness concerns, and usage concerns, and the developed scale had good reliability and validity, achieving a quantitative study of privacy concerns and providing a basis for future empirical studies related to the discussion of privacy concerns.